Green post-communism? : environmental aid, Polish innovation, and evolutionary political economics - Sandberg, Mikael (Routledge studies of societies in transition, 1999)
In recent years the environmental situation of post-communist societies has been a topic of much debate. Green Post-Communism? asks whether foreign aid can help such societies to steer their technological innovation systems in more environmentally-sound directions. Throughout the book, Sandberg develops an 'evolutionary' approach to understanding innovation in political economic systems, taking the work of Joseph Schumpeter and Karl Deutsch as points of departure. Drawing together unique interviews with the first Polish aid recipients and previously unpublished ministerial information, Green Post-Communism? will be an important resource for economists, political scientists, environmentalists and aid institutions.